“Delicada e dedicada”: representações sociais do feminino em cartazes de campanhas publicitárias do Ministério da Saúde - Brasil, 2012 - Izabela Gonçalves Terra (2014)
The femininity models were socially constructed under the political and cultural contexts relevant in each historical period, reflecting in the feminine condition, in general, marked by gender inequalities. The social roles assigned to women manifest themselves through different communication formats and artistic production, which can be understood as social thought expression forms. This way, the Communication and Health publications are an important source for comprehending the meanings assigned to the feminine in Brazil. Taking into consideration that the media campaigns are important means of communication for the Health Ministry, the content of these campaigns reveal official positions and express socially shared elements among the creators. Thus, knowing the social representation of the feminine presented in such materials is a relevant objective for understanding the dimensions of the social thoughts in women health field, as guiding element in social practices. Taking into account the textual and pictorial elements present in such publications is considered relevant, facing the complementarity observed between both kinds for the message broadcasting. In the context of such questions, this study objects learning the feminine social representations presented in 16 posters released by the Health Ministry, on which feminine images were represented. These set of posters was subject to Semiotics Analysis and Content Analysis for the textual data assessment. The results show a duality on the representational contents, which cycles between the consolidated perspectives, related to the fragility and dedication to others, and more recent approaches, that associate themselves to the feminine self-care, to the professional performance, to the unrestricted socialization and to the autonomous sexuality. The findings point to a strong binding between the gender relations and health practices, as well as to the relevance of new investigations that contribute to understanding the social dynamics related to the feminine in the health field.